2012
DOI: 10.1186/1471-2334-12-159
|View full text |Cite
|
Sign up to set email alerts
|

Switch therapy in hospitalized patients with community-acquired pneumonia: Tigecycline vs. Levofloxacin

Abstract: BackgroundSwitch therapy is a management approach combining early discontinuation of intravenous (IV) antibiotics, switch to oral antibiotics, and early hospital discharge. This analysis compares switch therapy using tigecycline versus levofloxacin in hospitalized patients with community-acquired pneumonia (CAP).MethodsA prospective, randomized, double-blind, Phase 3 clinical trial; patients were randomized to IV tigecycline (100 mg, then 50 mg q12h) or IV levofloxacin (500 mg q24h). Objective criteria were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The present findings have important implications, since a lower risk for catheter-associated infections, reduced nursing workload, and decreased direct and indirect costs are associated with early IV-PO switches (4,5,(7)(8)(9). The proposed CDS algorithm allows for the implementation in most inpatient specialties with an openend intervention period; no manpower is required for the continued operation of the electronic reminders within the clinical information system, and a similar reminder could also be implemented in other hospitals.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The present findings have important implications, since a lower risk for catheter-associated infections, reduced nursing workload, and decreased direct and indirect costs are associated with early IV-PO switches (4,5,(7)(8)(9). The proposed CDS algorithm allows for the implementation in most inpatient specialties with an openend intervention period; no manpower is required for the continued operation of the electronic reminders within the clinical information system, and a similar reminder could also be implemented in other hospitals.…”
Section: Discussionmentioning
confidence: 94%
“…Under consideration of anticipated improvements due to the intervention (increase patient safety, reduce workload and costs) (2,4,5,(7)(8)(9) and of available studies with similar interventions that reported no higher incidence of adverse events, (9,11,13,18) a waiver for informed consent was requested, because (i) limiting the study to patients who could give informed consent would decrease the generalizability of the results, and (ii) even attempting to obtain informed consent from such a large number of patients would result in financial costs that are prohibitive and a potentially poor use of limited resources. The study was registered at ClinicalTrials.gov (NCT01499927).…”
Section: Design and Sitementioning
confidence: 99%
See 2 more Smart Citations
“…13 In the field of clinical research on CAP, time to clinical stability has been used as a clinical outcome to compare effectiveness of initial intravenous antibiotics. 15 During the initial 7 days of antimicrobial therapy, a number of patients will reach clinical stability. It can be hypothesized that those antibiotics with better activity against the etiologic organism may produce an early time to clinical stability and therefore increase the number of patients reaching clinical stability by day 7.…”
Section: Introductionmentioning
confidence: 99%